2018
DOI: 10.1016/j.ajic.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Changes in knowledge and attitudes of hospital environmental services staff: The Researching Effective Approaches to Cleaning in Hospitals (REACH) study

Abstract: To our knowledge, this is the first study to report changes in knowledge, attitudes, and perceived organizational support in environmental services staff members, in the context of a large multicenter clinical trial. In this underexplored group of hospital workers, findings suggest that environmental services staff members have a high level of knowledge related to cleaning practices and understand the importance of their role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 14 publications
1
37
0
1
Order By: Relevance
“…Our study has provided evidence of how difficult it is to implement communication change, reflecting the reality of large hospitals being complex institutions, usually with cleaning staff at the lower end of a strong and culturally-embedded staff hierarchy [17,21]. Nine of our 11 sites had some gaps in communication practices observed at baseline, and only three of these were able to record improvements in their communication component score.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Our study has provided evidence of how difficult it is to implement communication change, reflecting the reality of large hospitals being complex institutions, usually with cleaning staff at the lower end of a strong and culturally-embedded staff hierarchy [17,21]. Nine of our 11 sites had some gaps in communication practices observed at baseline, and only three of these were able to record improvements in their communication component score.…”
Section: Discussionmentioning
confidence: 87%
“…At each hospital during the pre-intervention period, the study team collected extensive baseline data about infection prevention and hospital cleaning using staff questionnaires [17], interviews, discussion groups, and the document review and hospital profile templates. For each hospital, contextual data were then systematically mapped against the implementation framework (additional file 2) and assessed to determine three separate sets of scores.…”
Section: Quantifying Implementationmentioning
confidence: 99%
“…Studies indicate that improving cleaning compliance and environmental surface cleanliness may be achieved with education and training utilizing auditing systems. [33,39,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] However, a recent study by Mitchell, White [77] reported that EVS staff have a high level of understanding in knowledge and of the importance of their role, but that there is a perceived lack of organizational support, investment in cleaning resources and feedback. When aiming to improve hospital cleanliness, the morale and attitudes of EVS staff must be considered as a determinant of the cleaning protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Pengetahuan perawat dapat berpengaruh terhadap peningkatan layanan rumah sakit dengan menjalankan praktik sesuai dengan SPO (Standart Operasional Prosedur) yang berlaku (Mitchell et al, 2018). Pengetahuan yang dimiliki oleh perawat merupakan ujung tombak dalam memberikan tindakan keperawatan pada pasien selama masa penugasan.…”
Section: Self-efficacyunclassified